Resilience and challenges of peritoneal dialysis survivors in the aftermath of the 2023 Kahramanmaraş earthquake - Sahutoglu, Tuncay; Danis, Ramazan; Pembegul, Irem; Ozturk, Ilyas; Huzmeli, Can; Tugcu, Murat; Kazancioglu, Rumeyza (Wiley, 2024)
IntroductionPeritoneal dialysis (PD) remains understudied in disaster nephrology. This retrospective multicenter study explores the experiences of PD survivors following the February 6, 2023, Kahramanmaras Earthquake.MethodsAdult PD patients from 11 affected cities were analyzed to assess challenges faced during and postearthquake, alongside clinical outcomes.ResultsAmong 101 participants (median age: 45 years, median PD duration: 24 months), 57 were female, with 79 on continuous ambulatory PD. Challenges included power outages and water shortages, with primary shelter in kin's houses (33%) and homes (28%). Twelve patients experienced PD program delays, and three lacked assistance postdisaster. Sixteen patients changed PD modalities, with seven experiencing postearthquake peritonitis. Clinical parameters remained stable, except for a slight decrease in hemoglobin levels.ConclusionDespite challenges, PD survivors exhibited resilience, highlighting the importance of addressing peritonitis and unusual pathogens in disaster preparedness initiatives.
Keywords: disaster; disaster nephrology; earthquake; peritoneal dialysis; peritonitis